PENGARUH DISPLAY PRODUK TERHADAP KEPUTUSAN PEMBELIAN: (Studi pada Aroma Bakery and Cake Shop Karya Jaya) - Afif, Muhammad Hamdan; Sriyanto, Dharmawan (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
Consumer purchasing decisions encompass the selection of products from an array of choices and the evaluation of the actual outcomes of those choices. An effective method to sway these decisions involves product displays, which create attractive mental images of the products and improve the overall in-store experience. This study delves into the influence of product displays on purchasing choices at Aroma Bakery and Cake Shop Karya Jaya, adopting a quantitative approach with an associative perspective. A sample of 96 respondents was selected through Accidental Sampling, and data were gathered through questionnaires and secondary sources. The data analysis included assessments of validity and reliability, classical assumption tests, simple linear regression analysis, hypothesis testing, and the computation of the coefficient of determination. The results unveil a substantial and positive association between product displays and purchasing choices (t-count = 9.332 > t-table, Sig < 5%), with product displays accounting for 48% of the variations in purchasing decisions. This research underscores the pivotal role of product displays in shaping consumer preferences at Aroma Bakery and Cake Shop Karya Jaya, underscoring their capacity to enrich the shopping experience and steer consumer selections.